2020
DOI: 10.1098/rsob.200112
|View full text |Cite
|
Sign up to set email alerts
|

RNA editing in mesothelioma: a look forward

Abstract: RNA editing is a post-transcriptional process increasing transcript diversity, thereby regulating different biological processes. We recently observed that mutations resulting from RNA editing due to hydrolytic deamination of adenosine increase during the development of mesothelioma, a rare cancer linked to chronic exposure to asbestos. This review gathers information from the published literature and public data mining to explore several aspects of RNA editing and their possible implications for cancer growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 145 publications
0
5
0
Order By: Relevance
“…In our previous studies [ 14 , 15 ] investigating mesothelioma development in mice exposed to crocidolite (blue asbestos), we observed increased RNA editing, and one of the genes that were significantly more edited in asbestos-exposed mice was Rbm8a ( Figure 2 A), suggesting that one possible post-transcriptional process controlling Rbm8a expression is RNA editing. Indeed, A-to-I editing can affect RNA stability, miRNA- or RNA-binding protein binding ability, and translational activity (recently reviewed in [ 16 ]). While no significant increase in Rbm8a mRNA expression was detected in asbestos-exposed mesothelium ( Supplementary Figure S2A ), we observed increased nuclear Rbm8a immunoreactivity in mesothelial cells and mesothelioma tumors upon asbestos exposure ( Figure 2 B), indicating that RNA editing coincided with increased protein levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies [ 14 , 15 ] investigating mesothelioma development in mice exposed to crocidolite (blue asbestos), we observed increased RNA editing, and one of the genes that were significantly more edited in asbestos-exposed mice was Rbm8a ( Figure 2 A), suggesting that one possible post-transcriptional process controlling Rbm8a expression is RNA editing. Indeed, A-to-I editing can affect RNA stability, miRNA- or RNA-binding protein binding ability, and translational activity (recently reviewed in [ 16 ]). While no significant increase in Rbm8a mRNA expression was detected in asbestos-exposed mesothelium ( Supplementary Figure S2A ), we observed increased nuclear Rbm8a immunoreactivity in mesothelial cells and mesothelioma tumors upon asbestos exposure ( Figure 2 B), indicating that RNA editing coincided with increased protein levels.…”
Section: Resultsmentioning
confidence: 99%
“…RNA editing is dependent on the activity of adenosine deaminase acting on double-stranded RNA (dsRNA) enzymes ADAR1 and ADAR2 (reviewed in [ 16 ]). Repetitive sequence elements play an essential role in the formation of dsRNA, as these have the ability to form double-stranded structures.…”
Section: Introductionmentioning
confidence: 99%
“…dsRNA is identified and destabilized by ADARs, thereby dampening the type-1 IFN induced inflammatory response (reviewed in(58)). Although in our previous study we had shown that murine mesothelioma cells bear a high basal level of IFN stimulated genes (ISGs) associated with high levels of endogenous retroviruses (16), in the absence of ADAR2 we observed (Fig.7A) an upregulation of the IFN-response with an increase in expression of the ISGs retinoic acid-inducible gene I (RIG-I) and IFN-induced transmembrane protein 1 (IFITM1) in both Mero95 and RN5 cells.…”
Section: Resultsmentioning
confidence: 99%
“…dsRNA is identified and destabilized by ADARs, thereby dampening the type-1 IFN induced inflammatory response (reviewed in (58)). Although in our previous study we had shown that murine mesothelioma cells bear a high basal level of IFN stimulated genes (ISGs) associated with high levels of endogenous retroviruses (16), in the absence of ADAR2 we observed (Fig.…”
Section: Adar2 and Tumor Microenvironmentmentioning
confidence: 99%
“…dsRNA is identified and destabilized by ADARs, thereby dampening the type‐1 IFN‐induced inflammatory response (reviewed in [ 63 ]). Although in our previous study we had shown that murine mesothelioma cells bear a high basal level of IFN stimulated genes (ISGs) associated with high levels of endogenous retroviruses [ 16 ], in the absence of ADAR2 we observed (Fig.…”
Section: Resultsmentioning
confidence: 99%